Building financial performance through corporate social responsibility and value investing: A study in Indonesia - Karyatun, Subur; Soelton, Mochamad (Edelweiss Applied Science and Technology, 2025)
Recent research emphasizes the importance of implementing Good Corporate Governance (GCG) in improving the sustainability of financial performance (FM) for companies. The sustainability of this research, which includes Corporate Social Responsibility (CSR) as a mediating variable and Value Investing (VI) as a moderating variable, shows that the integration of GCG and CSR in a single model is still limited and requires further testing. Therefore, this study aims to examine the influence of CSR on the relationship between GCG and FM, particularly in the hospitality industry. The research employs an observational approach, distributing questionnaires to hotel managers in the Jakarta area using cluster sampling techniques. The research design is causal-predictive, and direct and indirect relationship analyses were conducted using the Partial Least Squares – Path Modelling (PLS-PM) method with the WarpPLS version 7.0 application. The analysis results indicate that GCG has a direct positive influence on CSR and FM, and CSR also contributes positively to FM. Furthermore, CSR was found to be a significant mediator in the relationship between GCG and FM. Although VI has the potential to act as a moderator in the relationship between GCG and FM, as well as CSR and FM, these findings provide important contributions to the hotel industry in designing effective GCG strategies to strengthen financial performance and support organizational sustainability. Translated with DeepL.com (free version).